(untitled) (World Science, 2020)
The purpose of the study: to evaluate the effectiveness of the proposed set of preventive measures for pregnant women after ART with a high risk of preeclampsia. Material and methods. To test the effectiveness of the proposed set of prophylactic measures, 60 pregnant women after ART were selected, which were randomly divided into 2 groups: 30 women who received the recommended complex (main group) and 30 women (comparison group), whose preeclampsia was prevented by order of the Ministry of Health. № 417 "Guidelines for the provision of outpatient obstetric and gynecological care." Results. The use of the recommended measures improves lipid metabolism (significant reduction of triglycerides and low density cholesterol), eliminates vitamin D deficiency, balances the cytokine profile (reduction of proinflammatory focus), reduces the prothrombotic potential of the hemostasis system (reduction of D-dimer and background marker damage). Improving the general condition and the use of psychotherapy can reduce the manifestations of vegetative-vascular dystonia, anxiety and improve quality of life. Such changes provide a more favorable background for the development of gestation. The incidence of preeclampsia decreased by 43.8% (from 26.7 to 15.0%), and mainly due to early preeclampsia, the incidence of which decreased by 78%, no cases of severe preeclampsia were reported. The frequency of placental insufficiency, fetal distress and growth retardation is reduced. The frequency of birth of children in a state of asphyxia is reduced by 2 times (up to 20.0 vs. 46.7%), severe asphyxia is not observed. Significantly lower and the frequency of violations of the period of neonatal adaptation (30.0 vs. 53.3%). Conclusions. The use of treatment and prophylactic complex to prevent preeclampsia in pregnant women after ART can improve a woman’s homeostasis, balance vegetative-vascular regulation, reduce the incidence of preeclampsia by 43.8% (from 26.7 to 15.0%) and other complications of pregnancy and childbirth, improve perinatal outcomes. Proven medical, social and economic efficiency of the developed complex allows to recommend it for implementation in medical practice.